2013
DOI: 10.1007/s00125-013-2869-1
|View full text |Cite
|
Sign up to set email alerts
|

Insulin signalling mechanisms for triacylglycerol storage

Abstract: Insulin signalling is uniquely required for storing energy as fat in humans. While de novo synthesis of fatty acids and triacylglycerol occurs mostly in liver, adipose tissue is the primary site for triacylglycerol storage. Insulin signalling mechanisms in adipose tissue that stimulate hydrolysis of circulating triacylglycerol, uptake of the released fatty acids and their conversion to triacylglycerol are poorly understood. New findings include (1) activation of DNA-dependent protein kinase to stimulate upstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
164
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(172 citation statements)
references
References 247 publications
6
164
0
2
Order By: Relevance
“…The systemic effects of WAT largely reflect its role in the control of blood lipid levels, as well as in the secretion of numerous bioactive peptides (e.g., adiponectin, leptin) from WAT cells (5,6). Adipocytes also release lipid-based mediators such as branched fatty acid esters of hydroxy fatty acids (FAHFAs) (7) and palmitoleate (8), which could improve local and whole-body glucose metabolism (9,10). Moreover, FAHFA administration also stimulated glucagon-like peptide 1 and insulin secretion, and reduced obesity-associated WAT inflammation in mice through cell surface G-protein-coupled receptor 120-dependent signaling (7).…”
mentioning
confidence: 99%
“…The systemic effects of WAT largely reflect its role in the control of blood lipid levels, as well as in the secretion of numerous bioactive peptides (e.g., adiponectin, leptin) from WAT cells (5,6). Adipocytes also release lipid-based mediators such as branched fatty acid esters of hydroxy fatty acids (FAHFAs) (7) and palmitoleate (8), which could improve local and whole-body glucose metabolism (9,10). Moreover, FAHFA administration also stimulated glucagon-like peptide 1 and insulin secretion, and reduced obesity-associated WAT inflammation in mice through cell surface G-protein-coupled receptor 120-dependent signaling (7).…”
mentioning
confidence: 99%
“…The acute increase in circulating insulin induced by food intake promotes nutrient storage in its major peripheral target tissues, primarily by stimulating: (1) glucose uptake in adipose tissue and muscle; (2) glycolysis and glycogen synthesis in muscle and liver; (3) lipogenesis in adipose tissue and liver and (4) protein synthesis in muscle and liver. Conversely, insulin has repressive functions on glycogenolysis, lipolysis and protein breakdown, as well as gluconeogenesis and ketogenesis in the liver (Taniguchi et al 2006, Cheng et al 2010, Czech et al 2013. Insulin may also exert local autocrine effects to promote beta-cell growth and survival, as well as influence its own production and secretion ( Fig.…”
Section: Insulin As a Key Metabolic Hormonementioning
confidence: 99%
“…Biochemical studies have shown that insulin plays key roles in regulating white adipocyte lipid accumulation, by inhibiting lipolysis as well as promoting fatty acid uptake and triglyceride synthesis (lipogenesis) and also by stimulating the expression of genes involved in lipid uptake and storage (Kersten 2001, Czech et al 2013 (Fig. 2).…”
Section: Direct Mechanisms By Which Insulin May Influence Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin-dependent inhibition of lipolysis is mediated through PKB catalyzed phosphorylation and activation of cGMP-inhibited 3´,5´-cyclic phosphodiesterase B (PDE3B) [44] and perhaps also through downregulation of lipolytic gene transcription via inhibition of forkhead box protein O1 (FoxO1) [45] (Figure 3). …”
Section: Insulin Signalingmentioning
confidence: 99%